Programa educativo de canto coral en el mejoramiento de la concentración en estudiantes de primer grado de primaria en el centro educativo parroquial Nuestra Señora de Fátima Belén 2023 - Falcon Fajardo, Selva Kateri (2025)
A study was conducted to evaluate the effects of an educational program aimed at improving concentration in two groups of First Grade Primary Education students at CEP Nuestra Señora de Fátima. The study adopted a quasi-experimental design with a non-randomized control group. The sample included 60 girls, divided into two groups: the experimental group (30 girls from Section “A”) and the control group (30 girls from Section “B”). At the start of the study, both groups showed low levels of concentration, as measured by the Concentration Test by Díaz Langa (1996), adapted for Peru by Ruiz Alva (2000). Only the experimental group participated in the educational program. Upon completion of the program, the concentration test was re-administered. The results, analyzed using Student’s *t*-test, revealed a significant improvement in the concentration of the experimental group compared to the control group. The girls in the experimental group demonstrated improvements in all areas of concentration: breadth, oscillation, intensity, and control. In conclusion, the educational program was effective in significantly improving concentration in the experimental group. The recommendations emphasize the importance of promoting concentration from the earliest stages of life, based on these findings.